Farewell blues - Robinson, Maggie (Robinson, Maggie. Lady Adelaide mysteries., 2021)
"The Society Scandal of the Season... Lady Adelaide Compton had prepared herself to say goodbye forever to Detective Inspector Devenand Hunter. It would be a welcome relief not to get mixed up in any more murders, even if it meant never working alongside the handsome detective again...wouldn't it? But then Addie's prim and proper mother, Constance, the Dowager Marchioness of Broughton, is accused of murdering her secret lover, and there can't be enough gentlemen detectives on hand to find the truth. The dead Duke of Rufford appeared to lead a blameless life, but appearances can be deceiving. And unless Addie and Dev work together, Constance will hang-which is no one's idea of a happy ending"--